APLIKASI UV SPECTROSCOPY DAN METODE SIMCA UNTUK KLASIFIKASI KOPI LIBERIKA TUNGKAL JAMBI DAN KOPI LIBERIKA PROBOLINGGO - Sapto Kuncoro; Meinilwita Yulia; Diding Suhandy (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Tungkal Composite Jambi Liberika Coffee is one of the top qualities of Indonesian coffees that has received a geographic indication certificate (IGs). With its limited production and high prices, currently Tungkal Jambi Liberika coffee is one of the coffees that is prone to being counterfeited. The counterfeiting of Tungkal Jambi Liberika coffee is increasingly difficult to identify, especially in the form of ground roasted coffee. This study evaluated the potential application of UV spectroscopy technology to classify Tungkal Jambi Liberika coffee (with geographic indications) and normal Probolinggo Liberika coffee (non- geographic indications). A total of 120 samples for each Liberika coffee were prepared weighing 1 gram for each sample. Spectra measurements were carried out in the form of a coffee solution. Spectral data were taken using a UV-visible spectrometer with a wavelength interval of 200-400 nm (Genesys™ 10S UV-Vis, Thermo Scientific, USA). By using the average transformed spectra in the 250-350 nm interval, the differences between the two types of Liberika coffee can be clearly seen, especially at some wavelength peaks, namely 270 nm, 300 nm, 315 nm and 346 nm. The classification accuracy obtained for the SIMCA classification is 100% for both Tungkal Jambi Liberika and Probolinggo Liberika coffee. Keywords:   authentication, classification accuracy, Tungkal Jambi Liberika coffee, SIMCA, UV Spectroscopy